ADMINISTRATIVE POLITICIZATION OR CONTESTABILITY? HOW POLITICAL ADVISERS AFFECT NEUTRAL COMPETENCE IN POLICY PROCESSES. (16th March 2016) - ÖHBERG, PATRIK; MUNK CHRISTIANSEN, PETER; NIKLASSON, BIRGITTA
Abstract: There is limited empirical research on the extent to which politicized recruitment of ministerial advisers affects the quality of the policy process. In this article we take a novel step by looking at two possible consequences of increased political recruitment for the policy process: administrative politicization and contestability. We deploy a Most Similar Systems comparison of Denmark and Sweden and include survey answers from 657 civil servants in managerial positions. We find that political recruitment of top civil servants, such as Swedish state secretaries, restricts the access of the civil service to the minister, but it does not substantially politicize the policy process. Danish civil servants perceive themselves as more contested by the relatively few Danish political advisers than their Swedish colleagues. Our results imply that the organization of political advice is a crucial factor for politicization and contestability